(untitled) (Communicare: Journal for Communication Studies in Africa, 2022)
In this article the question is raised of what professionalism means in the context of South Africanjournalism, and if there are deviations from ideas of professionalism as defined in normativeliberal frameworks of the news media in terms of how South African journalists perceive their ownrole in society and as to how they define professionalism. The research is partially based on in-depth qualitative interviews with journalists from a crosssection of the South African news media, and asks questions about their own perceptions ofprofessional values and their own role in society. The interview findings point to South Africanjournalists articulating their role as one of neither watchdog nor lapdog – instead, the intervieweesall articulate their role as based on competing imperatives, in which concerns for the audience anda broader articulation of the public interest take precedent over more liberal conceptualisations ofthe role of journalism in democracy.